Correlation between Matrix Metalloproteinase-9 Matrix Expression and Clinicopathology in Colorectal Adenocarcinoma Not Otherwise Specified - Sembiring, Rica Friska; Intan, T. Kemala; Alferraly, T. Ibnu (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2024)
Background Matrix metalloproteinase-9 (MMP-9) is a member of the metalloproteinase enzyme that is often found in colorectal adenocarcinoma. MMP-9 is able to destroy basement membrane proteins and extracellular matrix which play a role in tumor cell invasion. Method Cross-sectional analytic study with 30 paraffin block samples diagnosed as colorectal adenocarcinoma NOS at H. Adam Malik General Hospital Medan. MMP-9 expression was assessed using immunohistochemical staining in the cytoplasm of tumor cells and cells in the stroma. Expression was assessed using the Quick Score method and was declared weak if the total value was 0-5 and strong if the total value was ≥6. Statistical analysis between MMP-9 expression and depth of invasion was carried out using Fisher's Exact and Mann-Whitney U tests. Results MMP-9 expression was significantly related to stage (p=0.01), depth of invasion (p=0.03), and stromal Tils (p=0.03) and not significantly related to gender (p=0.28) , age (p=0.82), tumor location (p=0.69), grading (p=0.26), lymph node involvement (p=0.53), metastasis (p=0.53), perineural invasion (p=0.25), lymphatic invasion (p=1.00), IMVI (p=0.531.00), EMVI (p=1.00), tumor budding (0.25). Conclusion MMP-9 expression can be used as an indication of prognosis and also helps clinicians, especially in the management of patients with colorectal adenocarcinoma NOS.